Greenhouse gas emission curves for advanced biofuel supply chains. Issue 12 (December 2017) - Daioglou, Vassilis; Doelman, Jonathan; Stehfest, Elke; Müller, Christoph; Wicke, Birka; Faaij, Andre; van Vuuren, Detlef
Abstract Most climate change mitigation scenarios that are consistent with the 1.5–2 °C target rely on a large-scale contribution from biomass, including advanced (second-generation) biofuels. However, land-based biofuel production has been associated with substantial land-use change emissions. Previous studies show a wide range of emission factors, often hiding the influence of spatial heterogeneity. Here we introduce a spatially explicit method for assessing the supply of advanced biofuels at different emission factors and present the results as emission curves. Dedicated crops grown on grasslands, savannahs and abandoned agricultural lands could provide 30 EJBiofuel  yr−1 with emission factors less than 40 kg of CO2 -equivalent (CO2 e) emissions per GJBiofuel (for an 85-year time horizon). This increases to 100 EJBiofuel  yr−1 for emission factors less than 60 kgCO2 e GJBiofuel −1 . While these results are uncertain and depend on model assumptions (including time horizon, spatial resolution, technology assumptions and so on), emission curves improve our understanding of the relationship between biofuel supply and its potential contribution to climate change mitigation while accounting for spatial heterogeneity. Here emission curves are developed for advanced biofuel supply chains to enhance understanding of the relationship between biofuel supply and its potential contribution to climate change mitigation while accounting for landscape heterogeneity.